2017
DOI: 10.1007/s11199-017-0776-5
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Body Esteem Scale with a U.S. College Student Sample: Evaluation, Validation, and Uses for the BES-R

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Studies conducted so far have specified the importance of BE, body image (BI), and body dissatisfaction among adolescents (59). Low BE is associated with lower overall SE (60,61) but also with behavioural and psychological problems, and other mental health issues (62,63). Some previous studies have indicated that BI dissatisfaction is related with some aspects of risky sexual behaviour.…”
Section: Introductionmentioning
confidence: 96%
“…Studies conducted so far have specified the importance of BE, body image (BI), and body dissatisfaction among adolescents (59). Low BE is associated with lower overall SE (60,61) but also with behavioural and psychological problems, and other mental health issues (62,63). Some previous studies have indicated that BI dissatisfaction is related with some aspects of risky sexual behaviour.…”
Section: Introductionmentioning
confidence: 96%
“…Higher mean scores from the items indicated greater levels of muscle dissatisfaction. Evidence for the reliability of the scale was shown in American male college students (Frost et al, 2018). The scale was also associated with body shame (Frost et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the reliability of the scale was shown in American male college students (Frost et al, 2018). The scale was also associated with body shame (Frost et al, 2018). The Cronbach’s α was .90 (95% CI [.88, .91]) in this sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body esteem is how a person gives an evaluation of the state of his body (Nelson, Kling, Wängqvist, Frisén, & Syed, 2018) (Olenik-Shemesh, Heiman, & Keshet, 2018). The evaluation can be positive, negative, or neutral Analysis of body esteem and social anxiety in late adolescents a (Frost, Franzoi, Oswald, & Shields, 2018). Positive body esteem means assessing the body positively such as: beautiful/handsome face, proportional height, and so on.…”
Section: Introductionmentioning
confidence: 99%